THE DETERMINATION OF TRANSPORT ROUTE AND VEHICLE OPERATING COSTS FOR WASTE COLLECTION TRUCK IN PURUK CAHU CITY - Saiful Alam & Iphan F. Radam (International Journal of Research Science and Management, 2019)
Problem that has always been a big issue in urban area is related to municipal solid waste. The problem is getting complex along with the increasing number of population which will result in garbage in the form of solid waste. The increasing number of population is proportional to the level of consumption and activities of the society, which will cause the increase of solid waste. This research will discuss about the analysis of the volume of solid waste, solid waste transportation route, and the number of rotation started from the process of collecting solid waste until the transportation to final landfill. This research also examines the Vehicle Operating Cost (VOC) for truck conventionally that carries the solid wastecollection of Puruk Cahu City. The process of collecting solid waste in PurukCahu City is conducted through two methods, namely collecting solid waste in trash bin by door-to-door technique on the route along the ways that are passed using dump truck with capacity of 8 m3 andthe second technique isusing hauled containersystem with capacity of 7.5 m3 by putting container that has been provided in certain locations spread in several places in PurukCahu City as the temporary disposal station (TPS). The volume of solid waste of PurukCahu City along the ways that are passed by the flatbed truck with stationary container system is 48.20 m3 per day and the volume of solid waste on truck hauled container system is 13.70 m3 per day.The transportation route for truck with stationary container system is divided into 6 zones of transportation and is conducted everyday. Transportation route for dump truck with hauled container system is divided into 7 zones. The average Vehicle Operating Cost for solid waste collection truckwith stationary container system is IDR.2,893.75/km/m3 and with hauled container system is 4,690.50/km/m3 .